Precision Medicine: Technological Impact into Breast Cancer Diagnosis, Treatment and Decision Making - Tilli, Tatiana Martins (2021)
Fundação Oswaldo Cruz. Centro de Desenvolvimento Tecnológico em Saúde. Plataforma de Oncologia Translacional. Rio de Janeiro, RJ, Brasil.